The legacy of Sacco and Vanzetti - Joughin, Louis; Morgan, Edmund M., Jr. (Edmund Morris), 1878-1966; Schlesinger, Arthur M. (Princeton, New Jersey : Princeton University Press, 1978)
"A definitive history of the case...notable alike for its clarity and its fairness....Professors Joughin and Morgan conclude that Sacco and Vanzetti were the victims of a sick society, in which prejudice, chauvinism, hysteria, and malice were endemic. Few who will read this moving work will doubt that they have proved their point."-The New York Times"This was not merely a trial in court nor even a sociological phenomenon in the history of the United States. It was a spiritual experience and setback which only a fundamentally healthy America could have endured....What influence was it that brought such world figures as Clarence Darrow, William Borah, H.G. Wells, Arnold Bennett, Edna St. Vincent Millay, George Bernard Shaw, Arthur Brisbane, William Allen White, Fritz Kreisler, Albert Einstein and others to plead for men entirely unknown to them? Joughin and Morgan tell you why with the clarity and thoroughness of scholars and with the authority which their long study, impartiality, and sincerity assure and guarantee. It is a book that will excite and anger you."-The New RepublicOriginally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- PREFACE -- CHIEF PERIODS OF THE SACCO-VANZETTI CASE -- CONTENTS -- INTRODUCTION -- PART I. THE LEGACY TO THE LAW: DOUBT -- Chapter I. WHAT HAPPENED -- Chapter II. THE BRIDGEWATER ASSAULT, THESOUTH BRAINTREE MURDERS, ANDTHE PLYMOUTH TRIAL -- Chapter III. THE DEDHAM TRIAL -- Chapter IV. LEGAL CONTROVERSY, JULY, 1921-AUGUST, 1927 -- Chapter V. AN UNPUBLISHED CHAPTER IN THE RECORD -- Chapter VI. THE LEGACY OF DOUBT -- PART II. THE LEGACY TO THE PEOPLE: CONFLICT -- Chapter VII. "MEN OF NORFOLK" -- Chapter VIII. TWO NATIONS -- Chapter IX. TWO NATIONS (Continued) -- Chapter X. AUGUST, 1927 -- Chapter XI. THE GOVERNOR AND HIS COMMITTEE -- Chapter XII. THE AFTERMATH: 1927-29 -- Chapter XIII. THE LEGACY OF CONFLICT -- PART III. THE LEGACY TO LITERATURE: FAITH. THE BEGINNINGS OF HISTORICAL JUDGMENT -- Chapter XIV. THE LITERATURE OF THE RECORD AND THE VERSE -- Chapter XV. THE PLAYS -- Chapter XVI. THE NOVELS -- Chapter XVII. THE MURDERERS -- Chapter XVIII. THE MIND AND THOUGHT OF VANZETTI -- Chapter XIX. THE LEGACY TO LITERATURE: FAITH. THE BEGINNINGS OF HISTORICALJUDGMENT -- ACKNOWLEDGMENTS -- CHAPTER REFERENCES -- BIBLIOGRAPHY -- INDEX
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Sacco-Vanzetti Trial, Dedham, Mass., 1921.; Trials (Murder) -- Massachusetts -- Dedham; Affaire Sacco et Vanzetti, Dedham, Mass., 1921.; Procès (Meurtre) -- Massachusetts -- Dedham; HISTORY -- General; LAW -- Civil Procedure; LAW -- Legal Services; POLITICAL SCIENCE -- Government -- Judicial Branch; Trials (Murder); Massachusetts -- Dedham; 1921